Guaranteeing the Health Rights of People with Disabilities in the COVID-19 Pandemic: Perspectives from China - Qi F; Wang Q (Dove Medical Press, 2020)
Fei Qi, Qi Wang Law School, Hainan University, Haikou, Hainan Province, People’s Republic of ChinaCorrespondence: Qi Wang Email hainan-equal-rights-research-group@outlook.comAbstract: The question of how to guarantee the health rights of people with disabilities, and their health equity in particular, is frequently neglected in infectious disease pandemics. The international response to the ongoing COVID-19 pandemic is no exception in this regard. This neglect is related to other forms of marginalization and exclusion, as people with disabilities are generally poorer and more vulnerable than their non-disabled counterparts. Sustainable Development Goal 3 lacks an appropriate human rights language that enshrines equality and inclusivity in pandemic prevention work and related policies and legislation; and, as a result, it does not sufficiently guarantee the health rights of people with disabilities. This paper draws on China’s pandemic prevention work to extract relevant lessons, and seeks to explain how decision-making systems and resource allocation mechanisms impact on the health rights of people with disabilities. It discusses the unique roles of justice and legislation in helping to guarantee the health rights of people with disabilities in an infectious disease pandemic, and concludes that future research should more closely consider how Sustainable Development Goal 16 can support Sustainable Development Goal 3.Keywords: COVID-19, health equity, laws, infectious disease pandemic, IDP, judicature, people with disabilities, sustainable development goal, SDG